2015
DOI: 10.3892/ol.2015.3576
|View full text |Cite
|
Sign up to set email alerts
|

SC1, an immunoglobulin-superfamily cell adhesion molecule, is involved in the brain metastatic activity of lung cancer cells

Abstract: Abstract. SC1 is a cell adhesion molecule that belongs to the immunoglobulin superfamily; this molecule was initially purified from the chick embryonic nervous system and was reported to exhibit homophilic adhesion activity. SC1 is transiently expressed in various organs during development and has been identified in numerous neoplastic tissues, including lung cancer and colorectal carcinomas. The present study focused on the encephalic metastasis of lung cancer cells with respect to the potential function of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Gicerin is almost entirely absent in mature tissues, being restricted to muscles and endothelial cells in blood vessels. However, gicerin has been found to be over expressed in various sporadic tumors in animals [11] [14]- [19] [22] [23] [24]. It has also been demonstrated that lymphoma cells strongly express gicerin in their membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Gicerin is almost entirely absent in mature tissues, being restricted to muscles and endothelial cells in blood vessels. However, gicerin has been found to be over expressed in various sporadic tumors in animals [11] [14]- [19] [22] [23] [24]. It has also been demonstrated that lymphoma cells strongly express gicerin in their membrane.…”
Section: Introductionmentioning
confidence: 99%